2022
DOI: 10.1590/fst.41622
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biosynthesized silver nanoparticles by Garcinia mangostana extract against human breast cancer cell line MCF-7

Abstract: Breast cancer is the greatest common malignancy in females. This syndrome represents a serious public health problem that needs additional study to define its prediction and specific treatment. MCF-7 is a usually used breast cancer cell line that has been spread for many years by multiple groups. It shows to be a suitable model cell line for breast cancer studies worldwide, including those concerning anticancer. Anticancer and anti-inflammatory influences are important to treat the threats of chronic inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(27 reference statements)
0
0
1
Order By: Relevance
“…TEM revealed that the AgNPs were spherical and polydispersed (figure 2(A)) with the size distribution of the AgNPs in the range of 5-47 nm and an average size of 23.1 ± 6.8 nm. The size and shape of the AgNPs were significantly different from previous studies [33][34][35][36], probably because of the synthetic conditions including the concentration of AgNO 3 , synthesis temperature, reaction time, and the mangosteen peel extraction procedure. In addition, the shape of the AgNPs was associated with the efficiency of antibacterial activity.…”
Section: Characterisation Of Agnpscontrasting
confidence: 75%
“…TEM revealed that the AgNPs were spherical and polydispersed (figure 2(A)) with the size distribution of the AgNPs in the range of 5-47 nm and an average size of 23.1 ± 6.8 nm. The size and shape of the AgNPs were significantly different from previous studies [33][34][35][36], probably because of the synthetic conditions including the concentration of AgNO 3 , synthesis temperature, reaction time, and the mangosteen peel extraction procedure. In addition, the shape of the AgNPs was associated with the efficiency of antibacterial activity.…”
Section: Characterisation Of Agnpscontrasting
confidence: 75%
“…Among various materials, nanoscale environmentally friendly methods to synthesize AgNPs, avoiding the use of hazardous chemicals and solvents for various biomedical applications [13,14]. Green chemical routes using extracts from natural resources such as mango, grape, pomegranate, pineapple, ginger, imperial crown leaves, moringa oleifera (drumstick tree), and citrus macroptera (wild orange), as well as chitin and chitosan, have shown promise in serving as both reducing and stabilizing agents, as evident from the literature [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%